Preparation method and application of biomass-based porous carbon material with high specific surface area

By using ammonium persulfate as an oxidant and initiator in the preparation of porous carbon materials, the catalyst is improved to activate chitosan, and the problems of low specific surface area and insufficient adsorption capacity of porous carbon materials in the prior art are solved, and the preparation of porous carbon materials with high specific surface area and strong adsorption properties are achieved.

CN119735188APending Publication Date: 2025-04-01SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411633784.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, when preparing porous carbon materials, the carbon precursor structure has a decisive impact on the material structure and performance, but it is difficult to accurately control the pore structure and size distribution, resulting in low specific surface area and insufficient methane adsorption capacity, which is difficult to meet the widespread application needs.

Method used

Ammonium persulfate is used as an oxidizing agent and initiator to improve the water solubility and copolymerization efficiency of chitosan through hydrothermal reaction, and improve the catalyst to activate chitosan and increase the specific surface area of ​​porous carbon materials.

Benefits of technology

The specific surface area of ​​porous carbon materials has been significantly improved to reach far exceeding 3000m2/g, enhancing its adsorption capacity to methane, and meeting a wider application demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735188A_ABST
    Figure CN119735188A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a biomass-based porous carbon material with a high specific surface area, and the preparation method comprises the following specific steps: mixing chitosan and ammonium persulfate, carrying out a hydrothermal reaction, mixing a hydrothermal reaction product with metal alkali, and carbonizing to obtain the biomass-based porous carbon material with the high specific surface area. The ammonium persulfate can be used as a strong oxidant of a hydrothermal reaction to modify the surface of the chitosan and oxidize the chitosan to improve the water solubility of the chitosan, and meanwhile, the ammonium persulfate can also be used as an initiator of a copolymerization reaction to generate free radicals to attack amino groups of chitosan molecules to form free radical intermediates, so that the activation energy of the reaction is reduced, and the reaction efficiency is improved. The specific surface area of the porous carbon material prepared by the scheme can exceed 4000 m < 2 > / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the application field of porous carbon materials, and in particular to a preparation method of a biomass-based porous carbon material with a high specific surface area and application thereof. Background Art

[0002] With the continuous growth of global energy demand, the development of efficient and sustainable energy storage materials has become the focus of material science research. Porous carbon materials have become an emerging material due to their excellent physical and chemical properties. The highly developed pore structure and huge specific surface area make porous carbon materials show broad application potential in catalysis, gas adsorption, energy storage and other fields.

[0003] The preparation methods of porous carbon materials include activation method, template method and sol-gel method, etc. These methods not only affect the pore structure and specific surface area of ​​the material, but also determine its special properties. The disadvantage is that these methods have high requirements for carbon precursors, which leads to increased preparation costs. At the same time, biomass resources have become an ideal choice for carbon precursors for the preparation of porous carbon materials due to their renewable, environmentally friendly, widely distributed, low price and abundant total amount. Through the carbonization method, the chemical bonds of bio-based materials are broken under high temperature and completely decomposed into small molecular carbons. The process is simple and practical. Therefore, the biomass-based carbonization method has become a direct process for preparing porous carbon materials.

[0004] However, when preparing porous carbon materials by carbonization, the structure of the carbon precursor has a decisive influence on the structure and properties of the carbon materials. As the sources of biomass are diverse, the structures and element contents of different biomasses are different. It is still challenging to precisely control the pore structure and size distribution of the final porous carbon materials. Although the existing technology uses metal nanocatalysts or eutectic salts as reaction catalysts, the carbonization time is relatively long during the preparation process, and the specific surface area of ​​the resulting porous carbon materials is less than 3000m 2 / g, and its adsorption capacity for methane is less than 0.5g / g, which is difficult to meet current usage needs. Therefore, it is still of great significance to synthesize biomass-based porous carbon materials with high specific surface area and realize their wider application. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for preparing a biomass-based porous carbon material with an ultra-high specific surface area and its application, using ammonium persulfate as an oxidant and initiator to improve the water solubility of chitosan and the efficiency of copolymerization reaction. The improvement of the catalyst significantly improves the properties of the biomass-based material chitosan, activates it during the carbonization process, and increases the specific surface area of ​​the product.

[0006] A method for preparing a biomass-based porous carbon material with a high specific surface area, characterized in that it comprises the following steps:

[0007] Chitosan, ammonium persulfate and deionized water are uniformly mixed and then subjected to hydrothermal reaction;

[0008] The hydrothermal reaction product is cooled to 23-27°C, and then washed, filtered and dried to obtain an intermediate product;

[0009] The intermediate product is mixed evenly with a metal base, then ground and carbonized to obtain a carbonized product;

[0010] The carbonized product is pickled, washed and dried to obtain a biomass-based porous carbon material with a high specific surface area.

[0011] The hydrothermal reaction includes three stages: chain initiation, chain growth and chain termination. In the chain initiation reaction of chitosan and ammonium persulfate, ammonium persulfate as an initiator will produce primary free radicals, attack the chemical bonds between chitosan C2 and C3, and the chemical bonds are broken to form chitosan macromolecular free radicals. These chitosan macromolecular free radicals are more water-soluble than chitosan monomers, and have a higher effective solubility concentration in deionized water, which is beneficial to the output of the reaction. At the same time, chitosan macromolecular free radicals will react with each other or with other free radicals generated by the decomposition of ammonium persulfate to complete the chain growth reaction and further form chitosan chains or cross-linked structures. These reaction products can be used as precursors for carbonization. With the interaction between the free radicals, chain breaking and reaction termination occur, ending the reaction.

[0012] Preferably, the mass ratio of chitosan, ammonium persulfate and deionized water is 2:1-4:50. Furthermore, the mass ratio of chitosan and ammonium persulfate is preferably 2:2. This mass ratio can fully oxidize and graft chitosan while avoiding excessive consumption and waste of ammonium persulfate.

[0013] Preferably, the hydrothermal reaction temperature is 180-200° C., and the hydrothermal reaction time is not less than 6 hours. High temperature can activate the oxidation activity of ammonium persulfate and improve the oxidation efficiency, while a longer reaction time ensures the continuous progress of the copolymerization reaction.

[0014] Preferably, the washing is to rinse the product with deionized water at least 3 times, and the pH value of the product after washing is 6-8. Deionized water washing can remove part of the reaction by-products and soluble inorganic salt impurities, thereby improving the purity of the product.

[0015] Preferably, the drying temperature is 60-100° C., and the drying time is 12-24 hours. Drying and dehydration are necessary steps before grinding. The moisture in the intermediate product will cause the metal base hydrolysis to fail and affect the carbonization effect.

[0016] Preferably, the metal base is potassium hydroxide or sodium hydroxide.

[0017] Preferably, the mass ratio of the intermediate product to the metal base is 1:1-3. An appropriate excess of the metal base can improve the pore-forming effect and increase the specific surface area of ​​the product.

[0018] Preferably, the carbonization is to place the ground mixture in a nitrogen or inert gas protection of 60-100 mL / min, heat it to 800°C at a rate of 2-10°C / min, and keep it for 2 hours. Grinding and mixing first and then carbonizing can fully reduce the activation energy of the metal base carbonization reaction, promote the formation of pore structure, and increase the specific surface area of ​​the carbonized material.

[0019] Preferably, the acid washing is to immerse the carbonized product in a 1-2 mol / L hydrochloric acid or sulfuric acid solution and continuously stir for 4-24 hours. The purpose of the acid washing is to remove the remaining metal alkali during the carbonization process. Continuous stirring of the acid solution can fully neutralize the excess alkali to avoid affecting the adsorption performance of the final product.

[0020] Preferably, the drying temperature is 60-100°C and the drying time is 10-36 hours. Drying is a prerequisite for the product to have gas adsorption function. The porous carbon material after acid washing and water washing has a high moisture content and poor adsorption performance. By drying and removing water, the carbon material is kept dry and the gas adsorption capacity is restored.

[0021] An application of a high specific surface area biomass-based porous carbon material, preferably, the application of the high specific surface area biomass-based porous carbon material in gas adsorption and energy storage. Compared with other materials, the advantages of porous carbon materials are high specific surface area and porosity, controllable pore structure, chemical and thermal stability, moisture resistance, etc. The high specific surface area and porosity make it rich in adsorption sites and strong adsorption capacity, while the controllable pore size helps it to be adjusted according to different energy storage or chemical catalysis needs.

[0022] Compared with the prior art, the beneficial effect of the present invention is that compared with conventional metal nanoparticle catalysts, ammonium persulfate is more stable and more efficient. Ammonium persulfate can be used as a strong oxidant for hydrothermal reaction to modify the surface of chitosan, making chitosan more water-soluble and allowing the hydrothermal reaction to proceed more fully; it can also be used as an initiator for copolymerization, where ammonium persulfate produces a large number of free radicals that attack the chemical bonds of chitosan molecules to form chitosan macromolecular free radicals, which are grafted onto chitosan and react with each other to obtain long-chain polymers or crosslinked products, which are more efficient than copolymerization reactions using only chitosan monomers, reduce the activation energy of the reaction, and make it easier to synthesize high-molecular copolymers, thereby improving reaction efficiency. The present invention provides an efficient and feasible way to obtain carbon precursors for porous carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0025] In the attached figure:

[0026] Figure 1 : Nitrogen adsorption and desorption isotherms of different biomass-based porous carbon materials, where Figure A is APS1-K2 and APS1-K3, Figure B is APS2-K2 and APS2-K3, Figure C is APS4-K2 and APS4-K3, and Figure D is APS0-K2 and APS0-K3.

[0027] Figure 2 : 0-100nm pore size distribution diagram of different biomass-based porous carbon materials, among which Figure A is APS1-K2, Figure B is APS2-K2, Figure C is APS1-K3, and Figure D is APS2-K3.

[0028] Figure 3 : 0-100nm pore size distribution diagram of different biomass-based porous carbon materials, among which Figure A is APS4-K2, Figure B is APS0-K2, Figure C is APS4-K3, and Figure D is APS0-K3.

[0029] Figure 4 : CO2 adsorption curve of biomass-based porous carbon material APS2-K3 at 273K, 298K, and 313K under 0-1bar conditions (unit: mmol / g).

[0030] Figure 5 : CO2 adsorption curve of biomass-based porous carbon material APS2-K3 at 273K and 298K under 0-25bar conditions, where the measurement unit of Figure A is cm 3 / g, the measurement unit in Figure B is mmol / g.

[0031] Figure 6 : CO2 adsorption curve of biomass-based porous carbon material APS2-K3 at 273K under 0-100bar conditions, where the measurement unit of Figure A is mmol / g, the measurement unit of Figure B is cm3 / g, and the measurement unit of Figure C is g / g. DETAILED DESCRIPTION

[0032] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention all belong to the scope of protection of the present invention. Unless otherwise specified, the experimental materials, reagents, instruments, etc. used in the examples of the present invention are all commercially available; unless otherwise specified, all technical means in the examples of the present invention are conventional means well known to those skilled in the art.

[0033] Example 1 Preparation of porous carbon material APS2-K3

[0034] Add 2 g chitosan, 2 g ammonium persulfate, and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0035] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0036] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0037] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:3, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0038] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was dried in an oven at 80°C for 12 hours to obtain a porous carbon material APS2-K3.

[0039] Example 2 Preparation of porous carbon material APS1-K3

[0040] Add 2 g chitosan, 1 g ammonium persulfate, and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0041] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0042] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0043] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:3, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0044] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was dried in an oven at 80°C for 12 hours to obtain a porous carbon material APS1-K3.

[0045] Example 3 Preparation of porous carbon material APS4-K3

[0046] Add 2 g chitosan, 4 g ammonium persulfate, and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0047] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0048] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0049] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:3, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0050] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was dried in an oven at 80°C for 12 hours to obtain a porous carbon material APS4-K3.

[0051] Example 4 Preparation of porous carbon material APS2-K2

[0052] Add 2 g chitosan, 2 g ammonium persulfate, and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0053] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0054] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0055] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:2, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0056] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was dried in an oven at 80°C for 12 hours to obtain a porous carbon material APS2-K2.

[0057] Example 5 Preparation of porous carbon material APS1-K2

[0058] Add 2 g chitosan, 1 g ammonium persulfate, and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0059] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0060] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0061] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:2, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0062] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was dried in an oven at 80°C for 12 hours to obtain a porous carbon material APS1-K2.

[0063] Example 6 Preparation of porous carbon material APS4-K2

[0064] Add 2 g chitosan, 4 g ammonium persulfate, and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0065] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0066] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0067] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:2, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0068] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was dried in an oven at 80°C for 12 hours to obtain a porous carbon material APS4-K2.

[0069] Comparative Example 1 Preparation of porous carbon material APS0-K3

[0070] Add 2 g chitosan and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0071] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0072] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0073] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:3, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0074] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was placed in an oven and dried at 80°C for 12 hours to obtain a porous carbon material APS0-K3.

[0075] Comparative Example 2 Preparation of porous carbon material APS0-K2

[0076] Add 2 g chitosan and 50 mL deionized water into a 100 mL polytetrafluoroethylene reactor liner and mix well;

[0077] The reactor was covered with a reactor jacket and the lid was tightened, and then placed in a hydrothermal oven. The hydrothermal reaction temperature was set to 180° C. and the reaction time was 6 hours to obtain a hydrothermal reaction product.

[0078] After the reaction is completed, the reactor is taken out and cooled to 25°C, the hydrothermal product is taken out of the reactor, washed with deionized water and filtered for more than 3 times until the pH value of the product is 7, and then placed in an oven at 80°C for 24 hours to obtain an intermediate product;

[0079] The intermediate product and potassium hydroxide were added into a mortar at a mass ratio of 1:2, mixed evenly, and ground thoroughly. The evenly ground mixture was transferred into a nickel crucible and placed into a tube furnace. Nitrogen was introduced at a flow rate of 80 mL / min, and the temperature was increased to 800° C. at a rate of 3° C. / min, and maintained for 2 hours to obtain a carbonized product.

[0080] The carbonized product was immersed in a 2 mol / L hydrochloric acid solution for pickling for 6 hours, and then washed with deionized water for more than 3 times until the pH value of the product was 7. The washed product was dried in an oven at 80°C for 12 hours to obtain a porous carbon material APS0-K2.

[0081] Experimental Example 1 Analysis of the Micropore Properties of Porous Carbon Materials

[0082] The porous carbon materials of the embodiment and comparative example were tested by nitrogen adsorption method using 3Flex adsorption instrument produced by Micromeritics. The total pore volume was calculated according to the formula of relative pressure P / atmospheric pressure P0, and the pore structure was analyzed to obtain the main pore size distribution range.

[0083] Table 1 Analysis of micropore properties of different porous carbon materials

[0084]

[0085] From Table 1 and Figure 2 , 3 It can be seen that the main pore size distribution range of all porous carbon materials is 0-3nm, which meets the micropore requirements. Figure 1 It can be seen that, under the premise that the mass ratio of the hydrothermal reaction product and the metal base is consistent, the porous carbon material obtained by the mass ratio of chitosan to ammonium persulfate is 2:1-2 has a larger total specific surface area and micropore area, and a higher total pore volume. Compared with the control example without the addition of ammonium persulfate, under the same conditions, the overall properties of the porous carbon material with the addition of ammonium persulfate are better. Under the premise that the mass ratio of chitosan to ammonium persulfate is consistent, the properties of the porous carbon material obtained by the mass ratio of the hydrothermal reaction product to the metal base is 1:3 are better than the porous carbon material obtained by the mass ratio of the intermediate product to the metal base is 1:2. In summary, the most preferred parameters of the preparation method of this scheme are: the mass ratio of chitosan to ammonium persulfate is 2:1-2, and the mass ratio of the intermediate product to the metal base is 1:3. The total specific surface area of ​​the porous carbon materials (APS2-K3, APS1-K3) prepared under this condition is far more than 3000m 2 / g, which is significantly better than the performance of porous carbon materials prepared based on biomass-based materials in the prior art.

[0086] Experimental Example 2 Application of APS2-K3 in the field of gas adsorption

[0087] The porous carbon material APS2-K3 prepared in Example 1 was placed in a 300° C. environment and heated for 6 hours for degassing to ensure that there was no impurity gas on the sample surface.

[0088] The degassed APS2-K3 was placed in the Micromeritics ASAP2460 series gas physical adsorption instrument to test the CO2 adsorption capacity of the sample under different conditions.

[0089] The degassed APS2-K3 was placed in the H-Somb 2600 high temperature and high pressure adsorption instrument to test the adsorption capacity of the sample for CH4 under different conditions.

[0090] The test results are shown in Table 2.

[0091] Table 2 Gas adsorption of APS2-K3 under different test conditions

[0092]

[0093] From Table 2 and Figure 6 It can be seen that APS2-K3 has a good adsorption capacity for methane (CH4) at 0℃ (273K), with an adsorption capacity of 0.599g / g, which is far higher than the absorption capacity of porous carbon materials prepared by existing technologies for methane. Figure 4 , 5 It can be seen that under the test conditions, APS2-K3 also has a large adsorption capacity for carbon dioxide (CO2), which shows that APS2-K3 has a strong gas adsorption capacity and has good application prospects in adsorption and energy storage.

[0094] The above experimental results show that using ammonium persulfate as a catalyst, mixing chitosan with ammonium persulfate for hydrothermal reaction, and mixing the hydrothermal reaction product with a metal base and then carbonizing it can improve the microporous properties of the porous carbon material, improve the adsorption performance of the porous carbon material, and obtain a biomass-based porous carbon material with a high specific surface area.

[0095] It can be understood that the above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, the above technical features can be freely combined without departing from the concept of the present invention, and several deformations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the coverage of the claims of the present invention.

Claims

1. A method for preparing a biomass-based porous carbon material with a high specific surface area, characterized in that: The following steps are involved: Chitosan, ammonium persulfate and deionized water are uniformly mixed and then subjected to hydrothermal reaction; The hydrothermal reaction product is cooled to 23-27°C, and then washed, filtered and dried to obtain an intermediate product; The intermediate product is mixed evenly with a metal base, then ground and carbonized to obtain a carbonized product; The carbonized product is pickled, washed and dried to obtain a biomass-based porous carbon material with a high specific surface area.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the chitosan, ammonium persulfate and deionized water is 2:1-4:

50.

3. The preparation method according to claim 1, characterized in that: The hydrothermal reaction temperature is 180-200° C., and the hydrothermal reaction time is not less than 6 hours.

4. The preparation method according to claim 1, characterized in that: The washing comprises washing the product with deionized water for at least 3 times, and the pH value of the product after washing is 6-8.

5. The preparation method according to claim 1, characterized in that: The drying temperature is 60-100° C., and the drying time is 12-24 hours.

6. The preparation method according to claim 1, characterized in that: The metal base is potassium hydroxide or sodium hydroxide.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the intermediate product to the metal base is 1:1-3.

8. The preparation method according to claim 1, characterized in that: The carbonization process is to place the ground mixture in a nitrogen or inert gas atmosphere of 60-100 mL / min, heat it to 800°C at a rate of 2-10°C / min, and keep it for 2 hours. The carbonization process uses heat energy to directly destroy the chemical bonds in the chitosan, causing it to pyrolyze into small molecular carbon.

9. The preparation method according to claim 1, characterized in that: The acid washing is to immerse the carbonized product in a 1-2 mol / L hydrochloric acid or sulfuric acid solution and continue stirring for 4-24 hours.

10. The preparation method according to claim 1, characterized in that: The drying temperature is 60-100° C., and the drying time is 10-36 hours.

11. An application of a biomass-based porous carbon material with a high specific surface area, characterized in that: Application of the product described in claim 1 in gas adsorption and energy storage.